PEMANFAATAN TEKNOLOGI INFORMASI DAN PEMBELAJARAN KEWIRAUSAHAAN BAGI MAHASISWA IT: SYSTEMATIC LITERATUR REVIEW MENGGUNAKAN METODE PRISMA - Akbar, Syifa Chairunnissa Deliva; Very, Jhon (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study is a systematic literature review that aims to understand the influence of entrepreneurial learning and information technology utilization on the entrepreneurial interest of information technology (IT) students, especially in the context of digital startup development. Using the theoretical framework of planned behavior (TPB), this study identifies how entrepreneurship education directly shapes positive attitudes and subjective norms, while technological mastery increases students' perception of behavioral control. The PRISMA methodology was used to select and synthesize 25 empirical studies from different regions, focusing on the relationship between these variables. The results showed that the integration of the entrepreneurship curriculum and the mastery of technology synergistically strengthened students' intentions in starting start-ups, as well as changing their perception and motivation towards entrepreneurship. These findings affirm the importance of a holistic and interdisciplinary approach in preparing IT students as competent future technopreneurs in the digital age.  Keywords: Systematic literature, prism method, student entrepreneurship,                 entrepreneurial interest, digital startup Abstrak: Penelitian ini merupakan tinjauan literatur sistematis yang bertujuan untuk memahami pengaruh pembelajaran kewirausahaan dan pemanfaatan teknologi informasi terhadap minat berwirausaha mahasiswa teknologi informasi (TI), khususnya dalam konteks pengembangan startup digital. Dengan menggunakan kerangka teori of planned behavior (TPB), penelitian ini mengidentifikasi bagaimana pendidikan kewirausahaan secara langsung membentuk sikap positif dan norma subjektif, sementara penguasaan teknologi meningkatkan persepsi kontrol perilaku mahasiswa. Metodologi PRISMA digunakan untuk menyeleksi dan mensintesis 25 studi empiris dari berbagai kawasan, dengan fokus pada hubungan antara variabel-variabel tersebut. Hasil menunjukkan bahwa integrasi kurikulum kewirausahaan dan penguasaan teknologi secara sinergis memperkuat niat mahasiswa dalam memulai usaha rintisan, serta mengubah persepsi dan motivasi mereka terhadap kewirausahaan. Temuan ini menegaskan pentingnya pendekatan holistik dan interdisipliner dalam menyiapkan mahasiswa TI sebagai teknopreneur masa depan yang kompeten di era digital. Kata kunci: Litaratur sistematis, metode prisma, kewirausahaan mahasiswa, minat                    berwirausaha, startup digital